Approaches to the definition of the Baltic sea region - Klemeshev, Andrei P.; Korneevets, Valentin S.; Palmowski, Tadeusz; Studzieniecki, Тomasz; Fedorov, Gennady M. (Baltic Region, 2018)
The Baltic Sea region is one of the most developed and well-formed regions of international cooperation. It is a place for promoting collaboration between businesses, non-profits, public authorities, and municipalities of the countries located on the Baltic Sea coast and its adjacent territories. The Baltic Sea region has both unresolved problems and potential for development. This necessitates the identification of the Baltic Sea region territory having a capacity for the efficient development of mutually beneficial intergovernmental and international ties. A thorough overview of research literature, the implementation of international programmes and initiatives of international and intergovernmental organisations, and the application of the method of cartographic analysis have contributed to defining the territory of the Baltic region. The analysis shows three spaces that differ in the effect of the Baltic Sea on their territorial development. This approach proposes three definitions of the Baltic Sea region - a narrow, an extended, and a broad one, each serving a different purpose and being characterised by a different density of internal connections. According to the narrow definition, the region comprises the whole territories of Sweden, Denmark, Finland, Lithuania, Latvia, and Estonia and the coastal parts of Russia, Germany, and Poland. The extended definition adds the remaining part of Poland, most Russian and German regions, and Belarus and Norway. The broad definition of the Baltic region incorporates Iceland, some territories of Russia, Germany, the Czech Republic, Slovakia, and Ukraine.